2017
DOI: 10.1177/1471301217731171
|View full text |Cite
|
Sign up to set email alerts
|

Living with incontinence: The experience of people with dementia

Abstract: Dementia is a distressing condition in which individuals progressively require the support of others. Many people experience problems with incontinence and continence management.The presence of incontinence is influential in decisions for people with dementia to move into a care home. This study, in the interpretative tradition, investigates for the first time the person with dementia's perspective on these problems and their strategies for managing them.We conducted semi-structured conversational interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
(41 reference statements)
0
24
0
1
Order By: Relevance
“…The Consolidated Criteria for Reporting Qualitative (COREQ) Research guideline statement assists the reporting [ 16 ]. Ethical Approval was received from NHS Health Research Authority, London—City & East Research Ethics Committee (reference 18 LO 1836). This research was supported by funding from Alzheimer’s Society (grant number AS-JF-17-012).…”
Section: Methodsmentioning
confidence: 99%
“…The Consolidated Criteria for Reporting Qualitative (COREQ) Research guideline statement assists the reporting [ 16 ]. Ethical Approval was received from NHS Health Research Authority, London—City & East Research Ethics Committee (reference 18 LO 1836). This research was supported by funding from Alzheimer’s Society (grant number AS-JF-17-012).…”
Section: Methodsmentioning
confidence: 99%
“…While ISC may not be an option in patients with severe cognitive impairment, we found that patients with earlier/milder disease appear to still be suitable candidates. Research on continence in patients with cognitive impairment reveals that for disclosure of issues surrounding UI, the self-referral rate for UI among the elderly is lower [ 23 ]. Drennan et al recorded that carers would try to preserve patient dignity and therefore tended to under-report the extent of the problem(s) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that time and active listening were required for patients to reveal continence problems. Cole et al added to this by finding that patients often prefer not to complain as they do not want to burden the carer [ 23 ]. Of the many stigmas held by individuals and society, the shame associated with lack of self-control of urine and faeces can be very powerful [ 24 ], such as the human response to such a matter that powerful emotions and tensions can be triggered [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors are also associated with a greater financial burden, prolonged hospitalisation, re-admission, and increased mortality [ 29 31 ]. Incontinence is recognised as potentially emotionally demeaning [ 32 ], humiliating, and embarrassing [ 33 ] for the person, and combined with dementia, increases the stigma [ 34 ] PLWD already experience [ 35 – 37 ], which can have significant negative impacts on quality of life [ 38 ].…”
Section: Introductionmentioning
confidence: 99%